Energy-saving building material and application

By using sodium polyoxyethylene ether sulfate and dodecyl dimethyl betaine to form bubbles in building materials, and combining them with potassium dichromate pretreated fibers and polyoxyethylene-polyoxypropylene block copolymers, the heat insulation and crack resistance problems of existing building materials are solved, and the preparation of highly efficient, energy-saving and antibacterial building materials is achieved.

CN119285308AInactive Publication Date: 2025-01-10JIEXI JUTA CONCRETE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411645720.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing energy-saving building materials have poor thermal insulation and crack resistance, which affects the overall energy-saving effect and user experience of buildings.

Method used

Sodium sulfate of fatty acid polyoxyethylene ether and dodecyl dimethyl betaine are used to reduce the surface tension of the system and form uniform bubbles. Silicone polyether emulsion is added to enhance foam stability. At the same time, polypropylene fibers are pretreated with potassium dichromate solution and polyoxyethylene polyoxypropylene block copolymer is added to improve the dispersibility and bonding performance of the fibers in concrete.

Benefits of technology

It improves the thermal insulation and crack resistance of foamed concrete, enhances the stability and antibacterial properties of the material, extends its service life, reduces the thermal conductivity and crack formation of the material, and improves the overall energy-saving effect of the building.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005139646100000021
    Figure BDA0005139646100000021
  • Figure BDA0005139646100000051
    Figure BDA0005139646100000051
  • Figure BDA0005139646100000061
    Figure BDA0005139646100000061
Patent Text Reader

Abstract

The invention relates to an energy-saving building material and application, and belongs to the technical field of building materials, the energy-saving building material comprises the following raw materials: Portland cement, fly ash, fatty acid polyoxyethylene ether sodium sulfate, dodecyl dimethyl betaine, a silicone resin polyether emulsion, a pretreated fiber blend and deionized water; wherein the pretreated fiber blend is prepared from polypropylene fiber, a polyoxyethylene polyoxypropylene block copolymer, potassium dichromate and deionized water together. A large number of closed pores which are small in size and volume difference and good in stability are distributed in the foam concrete prepared according to the selected raw materials and formula, the heat transfer path in the material is increased, the average heat conductivity coefficient of the material is reduced, and the finished product has excellent heat insulation performance, so that the energy-saving effect is outstanding; meanwhile, the pretreated polypropylene fiber is doped into the concrete to disperse or bear the stress generated in the concrete, so that the finished product has excellent crack resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of building materials, and in particular, relates to an energy-saving building material and its application. Background Art

[0002] With the growth of global energy demand and concerns about environmental impact, the development of thermal insulation and energy-saving building materials has become an important way to reduce energy consumption and carbon emissions. By optimizing building materials, heat conduction can be reduced and the energy consumption of indoor appliances can be reduced. At present, most of my country's energy-saving and thermal insulation building materials are foam concrete, but the foam concrete on the market lacks thermal insulation and crack resistance, which affects energy saving and also provides poor user experience. Therefore, it is particularly necessary to provide a building material with better thermal insulation and crack resistance to improve the overall energy saving effect of the building. Summary of the invention

[0003] The purpose of the present invention is to provide an energy-saving building material and application, using fatty acid polyoxyethylene ether sodium sulfate and dodecyl dimethyl betaine to reduce the surface tension of the system, and forming a double electron layer on the surface of the system liquid film to surround the air to form a large number of uniform single bubbles, a large number of single bubbles thus form foam, and realize the preparation of foamed concrete; at the same time, in order to further enhance the stability of the foam, the present invention also adds a silicone resin polyether emulsion with excellent viscosity to provide good elasticity and self-repairing ability to the foam, thereby reducing its rupture and connectivity phenomenon and increasing the resistance of the foamed concrete to external forces, further improving the stability of the foam; the foamed concrete thus obtained has excellent thermal insulation performance, and therefore has an outstanding energy-saving effect. At the same time, the present invention uses potassium dichromate solution and polyoxyethylene polyoxypropylene block copolymer to pretreat polypropylene fibers, and the pretreated polypropylene fibers are mixed into concrete to disperse or bear the stress generated inside the concrete, so that the energy-saving building materials obtained have excellent crack resistance, solving the problem of poor thermal insulation and crack resistance of energy-saving building materials in the prior art.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] An energy-saving building material, comprising the following raw materials in parts by weight:

[0006]

[0007] As a preferred embodiment of the present invention, the preparation method of the pretreated fiber blend is as follows:

[0008] A1. Mix potassium dichromate and deionized water evenly and add concentrated sulfuric acid solution dropwise and stir evenly to obtain a mixed solution A;

[0009] A2, drying the polypropylene fiber to constant weight, adding the mixed solution A to soak, then controlling the temperature to react, and then raising the temperature to react, washing the polypropylene fiber after the reaction with deionized water, controlling the temperature to dry to constant weight, and obtaining an intermediate polypropylene fiber;

[0010] A3. Mix and stir the intermediate polypropylene fiber, the polyoxyethylene-polyoxypropylene block copolymer and deionized water under controlled temperature to obtain a pretreated fiber blend.

[0011] As a preferred embodiment of the present invention, the mass fraction of the concentrated sulfuric acid solution in step A1 is 75-80%.

[0012] As a preferred embodiment of the present invention, the usage ratio of potassium dichromate, concentrated sulfuric acid solution and deionized water in step A1 is 4-6 g:7-9 mL:95-100 mL.

[0013] As a preferred embodiment of the present invention, the usage ratio of the polypropylene fiber and the mixed solution A in step A2 is 2-3 g:105-115 mL.

[0014] As a preferred embodiment of the present invention, the soaking time in step A2 is 30-40 minutes; the temperature of the temperature control reaction is 70-75°C and the time is 6-10 minutes; the temperature rising reaction is to rise to 80-85°C and react for 10-15 seconds; the number of washing times is 5-7 times; and the temperature of the temperature control drying is 80-85°C.

[0015] As a preferred embodiment of the present invention, the mass ratio of the intermediate polypropylene fiber, the polyoxyethylene-polyoxypropylene block copolymer and the deionized water in step A3 is 0.6-0.8:1-2:4-8.

[0016] As a preferred embodiment of the present invention, the temperature of the temperature-controlled mixing and stirring in step A3 is 97-100° C. and the time is 0.5-1 h.

[0017] As a preferred embodiment of the present invention, the method for preparing the energy-saving building material comprises the following steps:

[0018] S1. Stirring silicate cement, fly ash and deionized water at controlled temperature to obtain slurry;

[0019] S2. Add the pretreated fiber blend and silicone resin polyether emulsion to the slurry in sequence, control the temperature and stir evenly, then add fatty acid polyoxyethylene ether sodium sulfate and dodecyl dimethyl betaine and stir evenly to obtain energy-saving building materials.

[0020] As a preferred embodiment of the present invention, the temperature for temperature-controlled stirring in step S1 is 26-28°C.

[0021] As a preferred embodiment of the present invention, the temperature for temperature-controlled stirring in step S2 is 25-28°C.

[0022] An application of energy-saving building materials, wherein the application of the energy-saving building materials includes but is not limited to being used for preparing roof insulation layers, preparing filling walls, preparing lightweight partition walls and roof panels, preparing roadbed backfill and strengthening roadbed reinforcement, etc.

[0023] Beneficial effects of the present invention:

[0024] (1) The present invention uses sodium polyoxyethylene fatty acid ether sulfate and dodecyl dimethyl betaine to reduce the surface tension of the system, and forms a double electron layer on the surface of the system liquid film to surround the air to form a large number of uniform single bubbles, and a large number of single bubbles thus form foam, thereby realizing the preparation of foamed concrete; at the same time, in order to further enhance the stability of the foam, the present invention also adds a silicone resin polyether emulsion with excellent viscosity to provide the foam with good elasticity and self-repairing ability, thereby reducing its rupture and connectivity and increasing the resistance of the foamed concrete to external forces, further improving the stability of the foam; in addition, dodecyl dimethyl betaine also has good antibacterial properties, can effectively inhibit the growth of microorganisms in concrete, prevent mold, corruption and other problems, thereby extending the service life of the energy-saving building material finished product;

[0025] The foam concrete thus produced has a large number of closed pores with small size difference and good stability distributed inside, which increases the heat transfer distance inside the material, reduces the average thermal conductivity of the material, and makes the finished product have excellent thermal insulation performance, thus having outstanding energy-saving effect.

[0026] (2) The present invention incorporates polypropylene fibers into concrete to disperse or bear the stress generated inside the concrete, thereby reducing the generation of cracks in the concrete and achieving an anti-cracking effect. At the same time, the present invention uses potassium dichromate solution to pretreat the polypropylene fibers, thereby increasing the roughness of the polypropylene fibers and leaving uneven grooves on the surface of the polypropylene fibers, thereby increasing the bonding performance between the polypropylene fibers and the concrete matrix. The addition of polyoxyethylene-polyoxypropylene block copolymer forms an adsorption film on the surface of the polypropylene fibers to increase the compatibility of the polypropylene fibers with concrete. At the same time, due to the presence of this adsorption film, the mutual attraction between the polypropylene fibers is reduced, making the polypropylene fibers easier to disperse in the concrete, promoting the uniform dispersion of the polypropylene fibers, and further enhancing the anti-cracking performance of the polypropylene fibers. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] A pretreated fiber blend is prepared. The preparation method of the pretreated fiber blend is as follows:

[0030] A1. Mix potassium dichromate and deionized water evenly and add 75% by mass concentrated sulfuric acid solution dropwise and stir evenly to obtain a mixed solution A;

[0031] The dosage ratio of the potassium dichromate, concentrated sulfuric acid solution and deionized water is 4g:8mL:95mL;

[0032] A2, drying the polypropylene fiber to constant weight, adding the mixed solution A prepared in step A1 to soak for 35 minutes after the drying, controlling the temperature to 75°C to react for 6 minutes after the soaking, and then heating to 83°C to react for 10 seconds after the reaction, washing the polypropylene fiber after the reaction with deionized water for 5 times, and then controlling the temperature to 83°C to dry to constant weight to obtain an intermediate polypropylene fiber;

[0033] The usage ratio of the polypropylene fiber and the mixed solution A is 3g:110mL;

[0034] A3, mixing the intermediate polypropylene fiber, the polyoxyethylene polyoxypropylene block copolymer and deionized water at 97° C. for 1 h to obtain a pretreated fiber blend;

[0035] The mass ratio of the intermediate polypropylene fiber, the polyoxyethylene-polyoxypropylene block copolymer and deionized water is 0.6:1.5:4.

[0036] The pretreated fiber blend prepared above is used as one of the raw materials to prepare energy-saving building materials, and the energy-saving building materials include the following raw materials in parts by weight:

[0037]

[0038] The preparation method of the energy-saving building material comprises the following steps:

[0039] S1. Stir the silicate cement, fly ash and deionized water at 26°C to obtain a slurry;

[0040] S2. Add the pretreated fiber blend and silicone resin polyether emulsion to the slurry in sequence, control the temperature at 28° C. and stir evenly, then add fatty acid polyoxyethylene ether sodium sulfate and dodecyl dimethyl betaine and stir evenly to obtain energy-saving building materials.

[0041] Example 2

[0042] A pretreated fiber blend is prepared. The preparation method of the pretreated fiber blend is as follows:

[0043] A1. Mix potassium dichromate and deionized water evenly and add 78% concentrated sulfuric acid solution dropwise and stir evenly to obtain a mixed solution A;

[0044] The dosage ratio of the potassium dichromate, concentrated sulfuric acid solution and deionized water is 6g:7mL:100mL;

[0045] A2, drying the polypropylene fiber to constant weight, adding the mixed solution A prepared in step A1 to soak for 30 minutes after drying, controlling the temperature to 70°C to react for 8 minutes after soaking, and then heating to 85°C to react for 15 seconds after the reaction, washing the polypropylene fiber after the reaction with deionized water for 7 times, and then controlling the temperature to 80°C to dry to constant weight to obtain an intermediate polypropylene fiber;

[0046] The usage ratio of the polypropylene fiber and the mixed solution A is 2g:105mL;

[0047] A3, mixing the intermediate polypropylene fiber, the polyoxyethylene polyoxypropylene block copolymer and deionized water at 98° C. and stirring for 0.5 h to obtain a pretreated fiber blend;

[0048] The mass ratio of the intermediate polypropylene fiber, the polyoxyethylene-polyoxypropylene block copolymer and deionized water is 0.67:2:8.

[0049] The pretreated fiber blend prepared above is used as one of the raw materials to prepare energy-saving building materials, and the energy-saving building materials include the following raw materials in parts by weight:

[0050]

[0051] The preparation method of the energy-saving building material comprises the following steps:

[0052] S1. Stir the silicate cement, fly ash and deionized water at 27°C to obtain a slurry;

[0053] S2. Add the pretreated fiber blend and silicone resin polyether emulsion to the slurry in sequence, control the temperature at 25° C. and stir evenly, then add fatty acid polyoxyethylene ether sodium sulfate and dodecyl dimethyl betaine and stir evenly to obtain energy-saving building materials.

[0054] Example 3

[0055] A pretreated fiber blend is prepared. The preparation method of the pretreated fiber blend is as follows:

[0056] A1. Mix potassium dichromate and deionized water evenly and add 80% by mass concentrated sulfuric acid solution dropwise and stir evenly to obtain a mixed solution A;

[0057] The dosage ratio of the potassium dichromate, concentrated sulfuric acid solution and deionized water is 5g:9mL:98mL;

[0058] A2, drying the polypropylene fiber to constant weight, adding the mixed solution A prepared in step A1 to soak for 40 minutes after drying, controlling the temperature to 72°C to react for 10 minutes after soaking, and then heating to 80°C to react for 13 seconds after the reaction, washing the polypropylene fiber after the reaction with deionized water for 6 times, and then controlling the temperature to 85°C to dry to constant weight to obtain an intermediate polypropylene fiber;

[0059] The usage ratio of the polypropylene fiber and the mixed solution A is 2.5 g:115 mL;

[0060] A3, mixing the intermediate polypropylene fiber, the polyoxyethylene polyoxypropylene block copolymer and deionized water at 100° C. for 1 h to obtain a pretreated fiber blend;

[0061] The mass ratio of the intermediate polypropylene fiber, the polyoxyethylene-polyoxypropylene block copolymer and deionized water is 0.8:1:6.

[0062] The pretreated fiber blend prepared above is used as one of the raw materials to prepare energy-saving building materials, and the energy-saving building materials include the following raw materials in parts by weight:

[0063]

[0064]

[0065] The preparation method of the energy-saving building material comprises the following steps:

[0066] S1. Stir the silicate cement, fly ash and deionized water at 28°C to obtain a slurry;

[0067] S2. Add the pretreated fiber blend and silicone resin polyether emulsion to the slurry in sequence, control the temperature to 27° C. and stir evenly, then add fatty acid polyoxyethylene ether sodium sulfate and dodecyl dimethyl betaine and stir evenly to obtain energy-saving building materials.

[0068] Comparative Examples 1-3

[0069] Compared with Example 3, the difference is that in the raw materials for preparing energy-saving building materials in Comparative Examples 1-3, the weight parts of fatty acid polyoxyethylene ether sodium sulfate, dodecyl dimethyl betaine and silicone resin polyether emulsion are as shown in Table 1, and the other operating steps and parameters remain unchanged.

[0070] Table 1

[0071]

[0072] Comparative Example 4

[0073] Compared with Example 3, the difference is that in the process of preparing the pretreated fiber blend in Comparative Example 4, potassium dichromate in step A1 is not added, and the other operating steps and parameters remain unchanged.

[0074] Comparative Example 5

[0075] Compared with Example 3, the difference is that in the process of preparing the pretreated fiber blend in Comparative Example 5, the polyoxyethylene-polyoxypropylene block copolymer of step A3 is not added, and the other operating steps and parameters remain unchanged.

[0076] Performance Testing

[0077] (1) Thermal insulation performance test:

[0078] The energy-saving building materials prepared in Examples 1-3 and Comparative Examples 1-3 were fully mixed and loaded into a test mold. During the loading process, the concrete in the test mold was rammed and the surface was smoothed to obtain a cubic test block with a size of 300 mm × 300 mm × 30 mm. The test block was cured at 20±2°C for 24 hours and placed in a curing box for standard curing of 28 days. The test block was placed in an oven at a temperature of (60±5)°C and dried to constant weight and then cooled to room temperature. The test standard refers to GB / T 10294-2008, and the results are shown in Table 2.

[0079] (2) Crack resistance test:

[0080] According to the standard GB / T 50081-2016, Examples 1-3 and Comparative Examples 4-5 were made into standard test blocks, and the number of cracks per unit area and the total cracking area per unit area were calculated 24 hours after the foam concrete was poured. The results are shown in Table 2.

[0081] Table 2

[0082]

[0083] It can be seen from the thermal conductivity data of Examples 1-3 and Comparative Examples 1-3 in Table 2 that the energy-saving building materials prepared by the present invention have excellent thermal insulation performance. This is because the present invention uses fatty acid polyoxyethylene ether sodium sulfate and dodecyl dimethyl betaine to reduce the surface tension of the system, and forms a double electron layer on the surface of the system liquid film to surround the air to form a large number of uniform single bubbles, and a large number of single bubbles thus form foam, thereby realizing the preparation of foamed concrete; at the same time, in order to further enhance the stability of the foam, the present invention also adds a silicone resin polyether emulsion with excellent viscosity to provide the foam with good elasticity and self-repairing ability, thereby reducing its rupture and connectivity and increasing the resistance of the foamed concrete to external forces, further improving the stability of the foam; the foamed concrete thus prepared has a large number of closed pores with small size difference and good stability distributed inside, which increases the heat transfer distance inside the material, reduces the average thermal conductivity of the material, and makes the finished product have excellent thermal insulation performance.

[0084] It can be seen from the crack resistance data of Examples 1-3 and Comparative Examples 4-5 in Table 2 that the energy-saving building material prepared by the present invention has an outstanding crack resistance effect. This is because the present invention mixes polypropylene fiber into concrete to disperse or bear the stress generated inside the concrete, thereby reducing the generation of cracks in the concrete and achieving an anti-crack effect; at the same time, the present invention uses chromic acid solution to pretreat the polypropylene fiber, increasing the roughness of the polypropylene fiber and leaving uneven grooves on the surface of the polypropylene fiber, thereby increasing the bonding performance of the polypropylene fiber and the concrete matrix; adding a polyoxyethylene polyoxypropylene block copolymer to form an adsorption film on the surface of the polypropylene fiber increases the compatibility of the polypropylene fiber with the concrete, and at the same time, due to the presence of this adsorption film, the mutual attraction between the polypropylene fibers is reduced, making the polypropylene fiber easier to disperse in the concrete, promoting the uniform dispersion of the polypropylene fiber, and then strengthening the crack resistance of the polypropylene fiber.

[0085] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0086] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. An energy-saving building material, characterized in that: The energy-saving building material comprises the following raw materials in parts by weight:

2. An energy-saving building material according to claim 1, characterized in that: The preparation method of the pretreated fiber blend is specifically as follows: A1. Mix potassium dichromate and deionized water evenly and add concentrated sulfuric acid solution dropwise and stir evenly to obtain a mixed solution A; A2, drying the polypropylene fiber to constant weight, adding the mixed solution A to soak, then controlling the temperature to react, and then raising the temperature to react, washing the polypropylene fiber after the reaction with deionized water, controlling the temperature to dry to constant weight, and obtaining an intermediate polypropylene fiber; A3. Mix and stir the intermediate polypropylene fiber, the polyoxyethylene-polyoxypropylene block copolymer and deionized water under controlled temperature to obtain a pretreated fiber blend.

3. An energy-saving building material according to claim 2, characterized in that: The usage ratio of potassium dichromate, concentrated sulfuric acid solution and deionized water in step A1 is 4-6 g:7-9 mL:95-100 mL.

4. The energy-saving building material according to claim 2, characterized in that: The usage ratio of the polypropylene fiber and the mixed solution A in step A2 is 2-3 g:105-115 mL.

5. The energy-saving building material according to claim 2, characterized in that: The soaking time in step A2 is 30-40 minutes; the temperature of the temperature control reaction is 70-75°C and the time is 6-10 minutes; the temperature rising reaction is to rise to 80-85°C and react for 10-15 seconds; the number of washing times is 5-7 times; the temperature of the temperature control drying is 80-85°C.

6. An energy-saving building material according to claim 2, characterized in that: The mass ratio of the intermediate polypropylene fiber, the polyoxyethylene-polyoxypropylene block copolymer and the deionized water in step A3 is 0.6-0.8:1-2:4-8.

7. The energy-saving building material according to claim 1, characterized in that: The preparation method of the energy-saving building material comprises the following steps: S1. Stirring silicate cement, fly ash and deionized water at controlled temperature to obtain slurry; S2. Add the pretreated fiber blend and silicone resin polyether emulsion to the slurry in sequence, control the temperature and stir evenly, then add fatty acid polyoxyethylene ether sodium sulfate and dodecyl dimethyl betaine and stir evenly to obtain energy-saving building materials.

8. An energy-saving building material according to claim 7, characterized in that: The temperature for temperature control and uniform stirring in step S1 is 26-28°C.

9. The energy-saving building material according to claim 7, characterized in that: The temperature for temperature control and uniform stirring in step S2 is 25-28°C.

10. An application of the energy-saving building material according to any one of claims 1 to 9, characterized in that: The energy-saving building material is used for preparing roof insulation layers, preparing filling walls, preparing lightweight partition walls and roof panels, and for roadbed backfilling and roadbed reinforcement.

Citation Information

Patent Citations

  • Multifunctional expandable fiber anti-cracking waterproof agent and preparation method

    CN108892414A

  • Novel energy-saving environmentally-friendly foam light soil used for subgrade and road beds and preparation method of foam light soil

    CN110002897A

  • High-ductility cement-based composite material and preparation method thereof

    CN113754382A